Syzygium cumini (jamun) therapeutic potential: a comprehensive review on phytochemical constituents and emphasis on its pharmacological actions related to diabetic intervention - Asanaliyar, Meharban; Nadig, Pratibha (International Journal of Basic & Clinical Pharmacology, 2020)
Syzygium cumini or Eugenia Jambolana Lam is a traditional medicinal plant very native to the Indian and Asian sub-continent. It is commonly known as black plum or jamun. Various plants parts of the tree are known for ethno-medicinal uses, and in particular, the fruits of Jamun tree are well known for medicinal uses and preparation of health drinks. Studies have shown that the berries contain carbohydrates, minerals and the pharmacologically active phytochemicals. The active phytochemical includes flavonoids, terpenes, and anthocyanins. Ayurvedic and Indian Folk Medicine have already mentioned the use of jamun for diabetic treatment even before the advent of insulin. The bark, fruit pulp, seeds and the leaves are evaluated in the crude form as well as extracts in various diabetic models. Further, bioactive phytochemicals are extracted using in vitro assays, some of them such as vitalboside-A, mycominose are also characterized with spectroscopic analysis. This review article is intended to compile Syzygium cumini’s therapeutic potential with special emphasis on the phytochemical constituents and its pharmacological activities related to diabetic intervention through recent studies conducted in last one decade. It also addresses the clinical and toxicological studies.